A First‐in‐Human Phase I Study of OPB‐111077, a Small‐Molecule STAT3 and Oxidative Phosphorylation Inhibitor, in Patients with Advanced Cancers. (6th March 2018) - Tolcher, Anthony; Flaherty, Keith; Shapiro, Geoffrey I.; Berlin, Jordan; Witzig, Thomas; Habermann, Thomas; Bullock, Andrea; Rock, Edwin; Elekes, Agnes; Lin, Chester; Kostic, Dusan; Ohi, Naoto; et al.
Abstract : Lessons Learned : OPB‐111077 is a novel inhibitor of STAT3 and mitochondrial oxidative phosphorylation that exhibited promising anticancer activity in preclinical models. In this first‐in‐human phase I study of OPB‐111077 in unselected advanced cancers, treatment‐emergent adverse events, most frequently nausea, fatigue, and vomiting, were generally mild to moderate in intensity and could be medically managed. Overall, only modest clinical activity was observed after OPB‐111077 given as monotherapy. Notable antitumor activity was seen in a subject with diffuse large B‐cell lymphoma. Background: OPB‐111077 is a novel inhibitor of STAT3 and mitochondrial oxidative phosphorylation with promising anticancer activity in preclinical models. Methods: Open‐label, phase I trial of OPB‐111077 in advanced cancers with no available therapy of documented benefit. Initial dose escalation in unselected subjects was followed by dose expansion. Patients received oral OPB‐111077 daily in 28‐day cycles until loss of clinical benefit. Results: Eighteen subjects enrolled in dose escalation, and 127 in dose expansion. Dose‐limiting toxicities were observed at 300 mg and 400 mg QD; maximum tolerated dose was defined as 250 mg QD. Frequently reported treatment‐emergent adverse events (TEAEs) included nausea, fatigue, and vomiting. TEAEs were generally mild to moderate and could be medically managed. OPB‐111077 reached micromolar drug concentrations, had an elimination half‐life of approximately 1 day, and reached steady‐state by day 8. A durable partial response was observed in one subject with diffuse large B‐cell lymphoma. Seven subjects with diverse tumor types had stable disease or minor responses for at least eight treatment cycles (224 days). Conclusion: OPB‐111077 is generally well tolerated, and its pharmacokinetic profile is sufficient for further clinical development. Notable clinical activity was observed in a subject with diffuse large B‐cell lymphoma. Overall, modest efficacy was observed against unselected tumors.